Odpowiedzi

Najlepsza Odpowiedź!
2009-12-29T19:40:51+01:00
Rozwiąż rownanie.
a) ( x-1) ( x-1) + x²- 1 = 2x²-2
x²-2x+1+x²-1=2x²-2
x=1

b) x² + (3x - 3) (x+1)= 1+( 2x-1)²
x²+3x²-3=1+4x²-4x+1
x=1
______________________________
rozwiąż równanie i spr. poprawność rozw.
(-6x +2)²= -3(4-12x²)

36x²-24x+4=-12+36x²
-24x=-16
x=16/24
x=2/3

Spr.
(-4+2)²=-3(4-12*4/9)
4=-12+16
4=4
Sprawdziłem :)

Pozdrawiam.
1 5 1
2009-12-29T19:45:25+01:00
A) tam na koncu chyba brakuje ci x

= x² - 2x +1 + x² -1 = 2x²-2
= 2x²- 2x= 2x² - 2

sorki zle zrozumialam pyt.
1 5 1
2009-12-29T19:46:50+01:00
( x-1) ( x-1) + x²- 1 = 2x²-2

x^2-2x+1+x^2-1=2x^2-2
-2x+1-1=-2
x=1

x² + (3x - 3) (x+1)= 1+( 2x-1)²

x^2+ 3x^2+3x-3x-3=1+4x^2-4x+1
-3=1-4x+1
4x=5
x=5/4

(-6x +2)²= -3(4-12x²)

36x^2-24x+4=-12+36x^2
-24x+4=-12
-24x=-16
x=16/24=2/3

sprawdzenie

L=(-6*2/3+2)^2=4
P=-3(4-12*(2/3)^2)=-12+16=4

L=P
wszystko jest ok
1 5 1